Modulation of Auxin Signaling and Development by Polyadenylation Machinery. Issue 2 (28th November 2018) - Zeng, Wei; Dai, Xinhua; Sun, Jing; Hou, Yifeng; Ma, Xuan; Cao, Xiaofeng; Zhao, Yunde; Cheng, Youfa
Abstract : A component of the polyadenylation machinery modulates auxin response and development. Abstract: Polyadenylation influences gene expression by affecting mRNA stability, transport, and translatability. Here, we report that Cleavage stimulation Factor 77 (AtCstF77), a component of the pre-mRNA 3ʹ-end polyadenylation machinery, affects polyadenylation site (PAS) selection in transcripts of some auxin signaling genes in Arabidopsis ( Arabidopsis thaliana ). Disruption of AtCstF77 reduced auxin sensitivity and decreased the expression of the auxin reporter DR5 - GFP . Null mutations of cstf77 caused severe developmental defects, but were not lethal as previously reported. cstf77 - 2 genetically interacted with transport inhibitor response 1 auxin signaling f - box 2 auxin receptor double mutants, further supporting that polyadenylation affects auxin signaling. AtCstF77 was ubiquitously expressed in embryos, seedlings, and adult plants. The AtCstF77 protein was localized in the nucleus, which is consistent with its function in pre-mRNA processing. We observed that PASs in transcripts from approximately 2, 400 genes were shifted in the cstf77 - 2 mutant. Moreover, most of the PAS shifts were from proximal to distal sites. Auxin treatment also caused PAS shifts in transcripts from a small number of genes. Several auxin signaling or homeostasis genes had different PASs in their transcripts in the cstf77 - 2 mutant. The expression levels of AUXIN RESISTANT 2 / INDOLE - 3 - ACETIC ACID 7 were significantly increased in the cstf77 - 2 mutant, which can partially account for the auxin resistance phenotype of this mutant. Our results demonstrate that AtCstF77 plays pleiotropic and critical roles in Arabidopsis development. Moreover, disruption of AtCstF64, another component of the polyadenylation machinery, led to developmental defects and reduced auxin response, similar to those of the cstf77 - 2 mutant. We conclude that AtCstF77 affects auxin responses, likely by controlling PAS selection of transcripts of some auxin signaling components.